Error analysis for a finite element approximation of elliptic dirichlet boundary control problems - May, Sandra; Rannacher, Rolf; Vexler, Boris (SIAM journal on control and optimization, 2013)
We consider the Galerkin finite element approximation of an elliptic Dirichlet boundary control model problem governed by the Laplacian operator. The analytical setting of this problem uses $L^2$ controls and a “very weak” formulation of the state equation. However, the corresponding finite element approximation uses standard continuous trial and test functions. For this approximation, we derive a priori error estimates of optimal order, which are confirmed by numerical experiments. The proofs employ duality arguments and known results from the $L^p$ error analysis for the finite element Dirichlet projection.